The Influence of Social Media on the Identity of the Young Generation - Maulida Zahraini; Nabila Malau; Ririn Tabita Subakti (Jurnal Pengetahuan Sosial dan Sejarah, 2025)
The purpose of this study is to determine the influence of social media on adolescent identity. The method used in this study is a literature study approach. This research will collect and analyze data from a variety of literature sources, including journals, articles, and other publications relevant to the topic. The influence of social media on adolescent identity. Literature study will be used to identify, review, interpret theories, concepts, and previous findings. With social media, teenagers will be easier to develop, for teenagers to interact and communicate. Social media is considered an ideal place to try to find self-identity. The ease of access to social media, but you still have to be wise in social media.